FAKTOR SOSIAL BUDAYA DAN PEMERIKSAAN KEHAMILAN YANG BERHUBUNGAN DENGAN KEJADIAN BBLR (Studi di Wilayah Kerja Puskesmas Singkawang Tengah di Kota Singkawang) - Julhana, Risa Alisanra; Hernawan, Andri Dwi; Saleh, Ismael (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2015)
Background : Low birth weight is defined as a birth weight of a liveborn infant of less than 2,500 g. It is considered as a major factor in the increase of mortality, morbidity, and disability in infants and children neonates. Also, it psychologically and physically raises long and short terms impacts for their future lives. The number of the low birth weight cases in Singkawang was 151 (3,9%) of 3.875 infants. In 2013, the same cases occurred at work area of Puskesmas Singkawang Tengah; 77 (5,93%) low birth weight cases and 3 mortality cases due to the low birth weight. Determinant factors of low birth weight cases were maternal, prenatal, and fetal factors. Therefore, this study is regarded important to be conducted as infants with low birth weight have significant contribution to mortality cases and are vulnerable to experience mental and physical developmental disorder.Objective : This study aimed at figuring out the correlation of social culture, prenatal care factors, and low birth weight cases.Methods : An observational analytic, as well as case control design, was carried out in this study. The respondents were divided into two groups; 22 case groups and 44 control groups. These sampling were grouped by using matching technique which includes age and parity. Then, the data were statistically analyzed by using Chi square test.Result : The study revealed two findings. First, the were correlation of parental roles (p value = 0,006; OR = 5,400), eating habits (p value = 0,015; OR = 4,333), and prenatal care (p value = 0,023; OR = 4,457). Second, there was no correlation of herbal medicine consumption and low birth weight cases.Conclusions : From the findings, the local public figures are encourage to socialize low birth weight preventions by providing grouped counseling and individual communication. Thus, the local people can increase their knowledge on nutrition and prenatal care information. At last, the cases of low birth weight can slowly be reduced.Keywords : parental roles, eating habits, herbal medicine, prenatal care, low birth weight